Basal Forebrain Cholinergic Activity Modulates Isoflurane and Propofol Anesthesia - Luo, Tian-Yuan; Cai, Shuang; Qin, Zai-Xun; Yang, Shao-Cheng; Shu, Yue; Liu, Cheng-Xi; Zhang, Yu; Zhang, Lin; Zhou, Liang; Yu, Tian; Yu, Shou-Yang (Frontiers in Neuroscience, 2020)
Cholinergic neurons in basal forebrain (BF) have long been considered to be the key neurons in the regulation of cortical and behavioral arousal, and cholinergic activation in the downstream region of the BF can arouse anesthetized rats. However, whether the activation of BF cholinergic neurons can induce the behavior and EEG recovery from anesthesia is unclear. In this study, based on a transgenic mouse line expressing ChAT-IRES-Cre, we applied a fiber photometry system combined with Gcamps expression in BF and found that both isoflurane and propofol inhibit the activity of BF cholinergic neurons, which is closely related to the consciousness transition. We further revealed that genetic lesion of BF cholinergic neurons was associated with a markedly increased potency of anesthetics, while DREADD activated BF cholinergic neurons was responsible for slower induction and faster recovery of anesthesia. We also documented a significant increase in δ power bands (1-4Hz) and decrease in β (12-25Hz) power bands in BF cholinergic lesioned mice, while a clearly noticeable decline in EEG δ power of activated BF cholinergic neurons. Moreover, sensitivity to anesthetics was reduced after optical stimulation of BF cholinergic cells, yet it failed to restore wake-like behavior in constant anesthetized mice. Our results indicate a functional role of BF cholinergic neurons in the regulation of general anesthesia. Inhibition of BF cholinergic neurons mediates the formation of unconsciousness induced by general anesthetics, and activation of them promotes the recovery from anesthesia state.